2006
DOI: 10.1080/01612840600840588
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Mothers Caring for Ventilator-Assisted Children at Home

Abstract: The complex management of ventilator-assisted children cared for in the home can place emotional and mental strain on parents, in particular, mothers. The purpose of this study was to explore the relationships among functional status of the child, impact of ventilator-assistance on the family, coping, social support, and depression in mothers caring for ventilator-assisted children at home. Thirty-eight mothers participated in the study. Almost half of the mothers experienced depressive mood symptoms. Impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 38 publications
9
82
0
Order By: Relevance
“…The CHIP subscale, Social support, Self-Esteem and Psychological Stability was significantly correlated with somatitization, depression, general health, and mental health (Blucker et al, 2011). Montagnino and Mauricio (2004) found significant correlations between the F-COPES subscale, Mobilizing Family to Acquire and Accept Help and several Impact on Family Scale subscales Blucker et al (2011);Kuster and Badr (2006); and P. B. Sullivan et al (2005) used general health questionnaires for data.…”
Section: Family Domainmentioning
confidence: 95%
See 2 more Smart Citations
“…The CHIP subscale, Social support, Self-Esteem and Psychological Stability was significantly correlated with somatitization, depression, general health, and mental health (Blucker et al, 2011). Montagnino and Mauricio (2004) found significant correlations between the F-COPES subscale, Mobilizing Family to Acquire and Accept Help and several Impact on Family Scale subscales Blucker et al (2011);Kuster and Badr (2006); and P. B. Sullivan et al (2005) used general health questionnaires for data.…”
Section: Family Domainmentioning
confidence: 95%
“…In two studies, authors describe the same population using cross-sectional (Toly, Musil, & Carl, 2012a) and longitudinal (Toly, Musil, & Carl, 2012b) designs. In two studies, investigators studied the same population analyzing differing variables in each study (Kuster & Badr, 2006;Kuster, Badr, Chang, Wuerker, & Benjamin, 2004). Both sets of authors used follow-up studies to clarify or expand original ideas around the functioning of families with CMC.…”
Section: Summary Of Studies Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that these mothers have emotional, social and physical problems such as trouble falling asleep, as they must wake up to check on the child or give it medicine, and they are socially isolated as well, scoring low on quality of life questionnaires (16)(17) . A survey of mothers of children on mechanical ventilation found that 45% displayed the signs and symptoms of depression (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Home nursing support, in particular night nursing, is important for the health and well-being of familial caregivers of children dependent on long-term MV [102]. Parents report regular disruption to their sleep [103] and the high demands related to the care of a child with long-term MV has been shown to be a significant risk factor for poor mental health outcomes of those mothers providing care at home [104]. The need for improved collaboration and communication between families and caregivers has also been cited as a source of stress for parents [57,105].…”
Section: Psychosocial Concernsmentioning
confidence: 99%